Recent advances in (4 + 3) cycloaddition of allenes - Yanyan Que; Wenli Lei; Yin Fang; Shuzhong He; Yang Chen (Green Synthesis and Catalysis)
Allenes are a class of unsaturated compounds containing a propadiene structural moiety, exhibiting essential physiological, pharmacological, and various reactivities. Their (4 ​+ ​3) cycloaddition reaction has become an effective method for synthesizing seven-membered rings, especially for heterocycles. This method has been continuously improved and developed. Herein, we review the (4 ​+ ​3) cycloaddition of allenes, focusing on the developed methodologies and the outlook in this field from 2013 to 2023.